Dorsomedial prefrontal cortex activation disrupts Pavlovian incentive motivation - Halbout, Briac; Hutson, Collin; Wassum, Kate M.; Ostlund, Sean B. (Frontiers in Behavioral Neuroscience, 2022)
The dorsomedial prefrontal cortex (dmPFC) is known to make important contributions to flexible, reward-motivated behavior. However, it remains unclear if the dmPFC is involved in regulating the expression of Pavlovian incentive motivation, the process through which reward-paired cues promote instrumental reward-seeking behavior, which is modeled in rats using the Pavlovian-instrumental transfer (PIT) task. The current study examined this question using a bidirectional chemogenetic strategy in which inhibitory (hM4Di) or excitatory (hM3Dq) designer G-protein coupled receptors were virally expressed in dmPFC neurons, allowing us to later stimulate or inhibit this region by administering CNO prior to PIT testing. We found that dmPFC inhibition did not alter the tendency for a reward-paired cue to instigate instrumental reward-seeking behavior, whereas dmPFC stimulation disrupted the expression of this motivational influence. Neither treatment altered cue-elicited anticipatory activity at the reward-delivery port, indicating that dmPFC stimulation did not lead to more widespread motor suppression. A reporter-only control experiment indicated that our CNO treatment did not have nonspecific behavioral effects. Thus, the dmPFC does not mediate the expression of Pavlovian incentive motivation but instead has the capacity to exert pronounced inhibitory control over this process, suggesting that it is involved in adaptively regulating cue-motivated behavior.